THE EFFECT OF WORK DISCIPLINE, WORK MOTIVATION, AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE IN THE DISTRICT OFFICE OF CEPOGO BOYOLALI - Beni Sutanto; Istiatin Istiatin; Fithri S. Marwati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Employee performance is defined as the quality and quantity of business results obtained by employees in carrying out their responsibilities. Performance refers to the entire work process, not simply the end result. Employee performance must be measured in order for the attainment of employee work results to be understood and evaluated further. The goal of this study was to assess the impact of work discipline, work motivation, and organizational commitment on the performance of Cepogo Boyolali District Office personnel. This study employs a quantitative technique, and the data used in this study are primary data gathered through questionnaires issued to 99 Cepogo Boyolali District Office personnel. The sampling technique utilized in this study is non-probability sampling, specifically saturated population individuals are used as samples. The validity test, reliability test, multiple linear regression, and statistical test t test were employed in this study. The SPSS for Windows version 24 program was used to test hypotheses. According to the findings of this study, work discipline, work motivation, and organizational commitment all have a favorable effect on employee performance. Job discipline, work motivation, and organizational dedication all have an impact on the success of Cepogo Boyolali District Office employees. Based on the findings of this study, the Cepogo Boyolali District Office is expected to pay more attention to work discipline, providing work incentive, and organizational commitment of its personnel in order to maximize performance. . Keywords: Work Discipline, Work Motivation, Organizational Commitment, Employee Performance, Cepogo Boyolali District